2017
DOI: 10.1080/0361526x.2017.1285127
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Expectations: Defining and Refining the Role of Technical Services in New Resource Rollouts

Abstract: From trial to implementation, technical services staff play an important role in shaping awareness and expectations of new or updated electronic resources. With appropriate message control during the rollout process, technical services staff can positively influence understanding and awareness of resources while keeping co-workers' and patrons' expectations in check. At the same time, by embracing this public service role, technical services acts as a full partner with public services in mediating resources to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They found that public services involvement "increased awareness and understanding of new and updated resources among public services staff and patrons, improved communications between technical and public services staff leading up to and following go-live and improved mediation of resources to patrons." 13…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that public services involvement "increased awareness and understanding of new and updated resources among public services staff and patrons, improved communications between technical and public services staff leading up to and following go-live and improved mediation of resources to patrons." 13…”
Section: Literature Reviewmentioning
confidence: 99%